Razlikovanje med stanjem in trpnikom na primerih iz Korpusa akademske slovenščine - Agović, Haris (Jezik in slovstvo, 2019)
The passive voice is quite rare in Slovenian due to a tradition that does not recommend its use except in certain types of text. In Slovenian, the passive voice is built with the participle with -n/-t or with se, although the form with se is quite rare. The problem arises when the participle does not express the passive voice but rather the state. There is a rule to distinguish the two meanings: when an active (or passive) construction is being transformed into a passive (or active) construction, the tense and the verbal aspect should not be changed. Based on examples from the corpus, it will be shown that this rule is not always correct.
Keywords: deležnik; deležnik stanja; Korpus akademske slovenščine; slovenščina; trpnik; tvornik